Peningkatan Kepatuhan Konsumsi Tablet Fe Pada Ibu Hamil Melalui Peran Tenaga Kesehatan Di Wilayah Kerja Puskesmas Kabupaten Asahan Tahun 2023 - Nur Indah Nasution; Indri Putri Nikanti (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Iron plays a crucial role in fetal growth, making its consumption essential for pregnant women. This community service journal discusses initiatives to enhance adherence to iron tablet consumption among pregnant women, involving the active participation of healthcare professionals in the Puskesmas Kabupaten Asahan area in 2023. The research aims to identify factors influencing pregnant women's adherence to iron tablet consumption and to develop intervention strategies involving healthcare professionals. The research methodology employs a participatory approach, engaging healthcare professionals and pregnant women as research subjects. Results indicate that factors such as knowledge, motivation, and social support significantly contribute to improving adherence to iron tablet consumption among pregnant women. Intervention approaches involving active roles of healthcare professionals, such as counseling, regular monitoring, and emotional support, have proven successful in increasing adherence levels. These findings serve as a foundation for developing more effective intervention programs to enhance the health of pregnant women in the working area of Puskesmas Kabupaten Asahan in 2023.